Publisher Correction: The long non-coding RNA HOXB-AS3 regulates ribosomal RNA transcription in NPM1-mutated acute myeloid leukemia - Dimitrios Papaioannou (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.